2018
DOI: 10.1016/j.ijbiomac.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Cell toxicity by ricin and elucidation of mechanism of Ricin inactivation

Abstract: Castor cake is a by-product of the extraction of oil from from seeds of castor plants (Ricinus communis). This by-product contains high levels of proteins, but a toxic protein, ricin, limits its use as an animal feed. Ricin can be efficiently inactivated by treatment with calcium oxide (CaO), which can be evaluated by a cytotoxicity assay using LLC-MK2 cells. The mechanism by which the CaO treatment inactivates ricin, however, is unclear. We report the structural changes responsible for ricin inactivation. Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Despite the very effective ricin-mediated rRNA depurination event that results in the inhibition of protein synthesis, it cannot be stated that these processes by themselves lead to cell death [24,30,31,32,33,203]. It has been demonstrated that ricin can induce apoptosis, autophagy and release of cytokine inflammatory mediators [25,26,27,28,29,30,204] (Figure 4).…”
Section: Cytotoxic Action Of Ricin On Cellsmentioning
confidence: 99%
“…Despite the very effective ricin-mediated rRNA depurination event that results in the inhibition of protein synthesis, it cannot be stated that these processes by themselves lead to cell death [24,30,31,32,33,203]. It has been demonstrated that ricin can induce apoptosis, autophagy and release of cytokine inflammatory mediators [25,26,27,28,29,30,204] (Figure 4).…”
Section: Cytotoxic Action Of Ricin On Cellsmentioning
confidence: 99%
“…34 , 44 The increased proteasome expression observed in the present study may thus act as a protective mechanism to prevent the aggregation of unfolded ricin A chain. 43 , 45…”
Section: Discussionmentioning
confidence: 99%
“…Ricin is a phytotoxin presented in seeds of Riccinus communis . It can be obtained both from the native seed as well as waste product obtained during extrusion of castor oil [69]. The castor plant grows wild in tropical and subtropical climates and the plant is cultivated in large scale for the commercial production of castor oil, a major component of the castor bean, with almost two million tons of seeds harvested annually.…”
Section: Introductionmentioning
confidence: 99%
“…The result is the inactivation of ribosomes in the cell and the blocking of protein synthesis, leading to cell death. A single ricin A chain is capable to inactivate approximately 1500 ribosomes per minute [69]. Toxicity results from the inhibition of protein synthesis, but other mechanisms are noted including apoptosis pathways, direct cell membrane damage, alteration of membrane structure and function, and release of cytokine inflammatory mediators [76].…”
Section: Introductionmentioning
confidence: 99%